The Link Between SRI and Financial Performance: Effects and Moderators - Revelli, Christophe; Viviani, Jean-Laurent (Management international / International Management / Gestiòn Internacional, 2013)
Over the last twenty years, the debate on financial performance of socially responsible investment (SRI) has not yielded a clear consensus, arguing mainly that there was no difference in performance between SRI and ‘conventional’ investment, although SRI could underperform or outperform in some cases. Our research, based on a meta-analysis ‘vote-counting’ approach of the empirical literature, allows us to observe that the effects of SRI on financial performance are multiple. Second, we conclude that the financial performance of SRI is radically changing according to the empirical methods employed by researchers.